Giải các phương trình sau:
a, 2x - 3 = 5x + 6
b, ( 2x + 1 ).( 3x - 2 ) = ( 5x - 8 ).( 2x + 1 )
c, \(\frac{2x+1}{3}-\frac{7x+5}{15}=\frac{2x-2}{5}\)
d,\(\frac{3x}{x-2}-\frac{x}{x-5}=\frac{3x}{\left(x-2\right).\left(5-x\right)}\)
e, ( x2 + 2x )2 + 9x2 + 18x + 20 = 0
Giúp ik a~
a , 2x -3 = 5x + 6
2x -5x=6+3
-3x = 9
x =9 :(-3)
x= -3
a) 2x-5x=3+6
-3x=9
x=-3
vậy........
b)(2x+1).(3x-2)-(5x-8).(2x+1)=0
(2x+1).(3x-2-2x-1)=0
(2x-1).(x-3)=0
==>x=1/2 ; x=3
c)(2x+1).5-(7x+5)=(2x-2).3
10x+5-7x-5=6x-6
3x=6x-6
3x-6x=6
-3x=6
x=-2